Study Of Relationship Between UTUAT Factors And Intention Towards Usage E-management In Libyan Petroleum Industry - Bashir Abuzwida; Zulkiplie Abd Ghani; Faizal Bin Kasmani (GIAP Journal, 2024)
Non-Indexed Publication